A method and separation system for removing ammonia from dry gas
Through the combination technology of modified hollow fiber membrane and electrooxidation method, the problem of high ammonia content in dry gas is solved, and the long-term operation of the ethylbenzene alkylation catalyst and the continuous regeneration of water washing water are achieved, reducing production costs.
Patent Information
- Application Number
- CN202111176396.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-10-09
AI Technical Summary
The high ammonia content in the dry gas in the prior art leads to a shortening of the operating cycle of the ethylbenzene alkylation catalyst and poor deamide effect, resulting in rapid saturation of the adsorbent and a large amount of water washing liquid consumption.
Modified hollow fiber membranes are used for membrane extraction, and the ammonia impurities in the dry gas of the raw material are removed through the water washing tower, and the ammonia-containing water washing liquid is back-extracted by using the modified hollow fiber membrane. Combined with electrooxidation, the rich liquid is degraded, so as to achieve continuous removal and regeneration of ammonia.
It effectively reduces the ammonia content in dry gas, extends the operating cycle of the ethylbenzene alkylation catalyst, reduces production costs, and realizes continuous purification and regeneration of washing water.
Smart Images

Figure CN115957595B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparing ethylbenzene from dry gas, and particularly relates to a method for removing ammonia from dry gas, in particular to a method for continuously removing trace ammonia from dry gas. Background Art
[0002] Dry gas refers to the tail gas that cannot be liquefied in the refinery, which mainly comes from the secondary processing of crude oil. The dry gas of oil refining enterprises mainly comes from catalytic cracking gas and is generally used as fuel. In order to make full use of this part of the dilute ethylene resources in the dry gas, improve the utilization rate of petroleum resources, and solve the current shortage of ethylbenzene / styrene market, the process of producing ethylbenzene from dry gas has been developed. The process of producing ethylbenzene from dry gas is generally to make the ethylene and a small amount of propylene and butene in the dry gas react with benzene under the action of a catalyst at a reaction temperature of 200℃-500℃ to produce ethylbenzene, propylbenzene, butylbenzene and polyalkylbenzenes.
[0003] Ethylbenzene alkylation catalysts generally use acidic molecular sieves. Due to the complexity of impurities in dry gas and the high concentration of ammonia in some refinery gases, the operation cycle of ethylbenzene alkylation catalysts is significantly shortened. In order to make the catalyst have a longer production cycle, the content of impurity ammonia generally needs to be controlled to less than 5ppm.
[0004] CN109574780A discloses a method for adsorbing ammonia in dry gas using modified activated carbon. Since the ammonia content in the dry gas is unstable and generally fluctuates greatly between 1 and 500 ppm, the adsorbent is easily saturated when the ammonia content is high, resulting in frequent loading and unloading of the adsorbent.
[0005] CN111450662A discloses a combined deammoniation process of a water washing tower, a cyclone separator, a coalescer and an adsorption tower, wherein the water washing liquid is selected from industrial water or an acidic aqueous solution, and the adsorbent is formed activated carbon, silicon dioxide, aluminum oxide, formed molecular sieve and strongly acidic cation exchange resin loaded with inorganic acid or organic acid, etc. In this process, since the operation flexibility of the water washing distillation tower is limited, when the ammonia content in the raw material fluctuates greatly, it is also difficult to effectively remove ammonia from the dry gas. Even if an adsorption tower is set up later, the adsorbent in the adsorption tower is quickly saturated due to the excessively high ammonia content in the dry gas.
[0006] "Study on the absorption of ammonia in phosphate fertilizer tail gas by rotating packed bed" (Chemical Intermediates, Issue 7, 2009) discloses a process for absorbing ammonia in phosphate fertilizer tail gas by using phosphoric acid wastewater. Compared with traditional tower equipment, the absorption efficiency of this process is improved to a certain extent, but the deammoniation effect is average.
[0007] In summary, the existing technology in the field of deamination has the main problems of low operational flexibility and average removal effect, which leads to continuous slow deactivation or rapid deactivation of alkylation catalysts. Therefore, the continuous and stable removal of trace ammonia in dry gas is one of the important issues that ethylbenzene units need to solve in the context of crude oil degradation. Summary of the invention
[0008] The technical problem to be solved by the present invention is that the ammonia content in dry gas is high and it is difficult to remove it continuously in the prior art, and a method for removing ammonia from dry gas is provided. The method of the present invention can be used to separate ammonia impurities in dry gas that significantly affect the activity of ethylbenzene alkylation catalysts, effectively eliminate the influence of ammonia impurities on the acid active sites of the catalyst, and is conducive to extending the operating cycle of the alkylation catalyst, and realizing low-cost and continuous production of ethylbenzene.
[0009] A first aspect of the present invention provides a method for removing ammonia from dry gas, comprising:
[0010] S1, the raw dry gas is washed with water to remove ammonia impurities through a water washing tower, the deammoniation purified dry gas is obtained at the top of the tower, and the ammonia-containing washing liquid is obtained at the bottom of the tower;
[0011] S2, stripping the ammonia-containing water washing liquid using a membrane extraction assembly equipped with a modified hollow fiber membrane, wherein the ammonia-containing water washing liquid and the ammonia stripping lean solution flow through the inner cavity and outer wall of the modified hollow fiber membrane respectively to obtain a deammoniation water washing liquid and an ammonia stripping rich solution;
[0012] S3, the ammonia stripping rich solution is degraded by electro-oxidation to obtain a regenerated ammonia stripping lean solution.
[0013] In the above technical scheme, in step S2, the modified hollow fiber membrane includes a base membrane, a grafted layer and an outer wall, wherein the carboxyl content in the base membrane is 3.8 to 11.2 mmol / g, and the sulfonic acid content is 1.9 to 8.4 mmol / g; the carboxyl content in the grafted layer is 14.4 to 32.4 mmol / g, and the sulfonic acid content is 7.2 to 24.3 mmol / g; the outer wall is a polydimethylsiloxane layer with a thickness of 80 to 160 microns.
[0014] In the above technical solution, the grafted layer is covered on the inner surface of the base film, and the outer wall is covered on the outer surface of the base film.
[0015] In the above technical solution, in step S2, the carboxyl content and sulfonic acid content in the base membrane of the modified hollow fiber membrane and the carboxyl content and sulfonic acid content in the grafted layer are based on per gram of modified hollow fiber membrane.
[0016] In the above technical solution, in step S2, in the modified hollow fiber membrane, preferably, the inner diameter of the modified hollow fiber is 0.3 to 1.0 mm.
[0017] In the above technical solution, in step S2, in the modified hollow fiber membrane, preferably, the base membrane thickness of the modified hollow fiber is 0.4 to 1.5 mm, and more preferably 0.5 to 1.2 mm.
[0018] In the above technical solution, the viscosity of the polydimethylsiloxane is 5000 to 10000 centipoise.
[0019] In the above technical solution, in step S2, in the modified hollow fiber membrane, the base membrane is a polypropylene membrane modified by a first modifier. The first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) and sodium polyanisyl sulfonate, and the mass fraction ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is (8-15):(2-6). The sodium poly(4-styrenesulfonic acid-co-maleic acid) is an equimolar copolymer of styrenesulfonic acid and maleic acid, with a molecular weight of 4000-7000, and the molecular weight of sodium polyanisyl sulfonate is 6000-10000. The molecular weight of the polypropylene is 40000-50000.
[0020] In the above technical solution, in step S2, the method for preparing the modified hollow fiber membrane comprises:
[0021] (1) preparing a basement membrane;
[0022] (2) coating the inner surface of the base film with a grafted layer;
[0023] (3) Then, an outer wall is coated on the outer surface of the base membrane to obtain a modified hollow fiber membrane.
[0024] In the above technical solution, preferably, the process of preparing the base membrane in step (1) comprises: preparing a casting liquid containing a first modifier, a core liquid and an outer gel bath, and then forming the hollow fiber membrane by hollow fiber spinning and drying to obtain a hollow fiber membrane, namely the base membrane.
[0025] In the above technical solution, preferably, the process of coating the graft layer on the inner surface of the base membrane in step (2) comprises: swelling the hollow fiber membrane, treating it with a second modifier, and treating it with a third modifier to coat the graft layer.
[0026] In the above technical solution, preferably, step (3) of coating the outer surface of the base membrane with an outer wall comprises: performing a third modification post-treatment on the hollow fiber membrane coated with the grafted layer obtained in step (2) to coat the hollow fiber membrane with a polydimethylsiloxane layer to obtain a modified hollow fiber membrane.
[0027] In the above technical solution, the first modifier described in step (1) is sodium poly(4-styrenesulfonic acid-co-maleic acid) and sodium polyanisyl sulfonate, and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is (8-15):(2-6). Wherein, sodium poly(4-styrenesulfonic acid-co-maleic acid) is an equimolar copolymer of styrenesulfonic acid and maleic acid, with a molecular weight of 4000-7000, and the molecular weight of sodium polyanisyl sulfonate is 6000-10000.
[0028] In the above technical scheme, the casting solution containing the first modifier in step (1) includes: polypropylene (molecular weight of 40,000 to 50,000), N-methylpyrrolidone, diethylene glycol, and the first modifier, wherein the mass ratio of polypropylene, N-methylpyrrolidone, diethylene glycol, and the first modifier is (20 to 30): (100 to 150): (2 to 6): (10 to 20). The preparation method of the casting solution containing the first modifier includes: stirring and mixing polypropylene, N-methylpyrrolidone, diethylene glycol, and the first modifier at 80 to 120° C. for 24 to 48 hours, and then standing and degassing for 5 to 10 hours to obtain the casting solution containing the first modifier. The core liquid is an N-methylpyrrolidone solution, wherein the mass concentration of the N-methylpyrrolidone solution is 2% to 8%. The outer gel bath is desalted water.
[0029] In the above technical scheme, the hollow fiber membrane molding described in step (1) can be obtained by a conventional spinning method. Among them, the spinning conditions are preferably as follows: the inner diameter and outer diameter of the spinneret are adjusted according to the inner diameter of the hollow fiber membrane and the thickness of the base membrane, the temperature of the core liquid and the outer gel bath is 0-3°C, the air gap height is 2-4 cm, the fiber collection rate is free fall, the flow rate of the casting liquid is 7-10 ml / min, the pressure of the casting liquid in the spinneret is 100-300 kPa (gauge pressure), the flow rate of the core liquid is 3-7 ml / min, the ambient temperature is 20-30°C, the ambient humidity is 50%-70%, and the casting liquid containing the first modifier undergoes solvent exchange with the core liquid and the outer gel bath and solidifies in phase separation to form a hollow fiber membrane blank. The hollow fiber embryo is washed with desalted water 4 to 8 times, low carbon alcohol (the low carbon alcohol is selected from at least one of methanol and ethanol) 4 to 8 times, and n-hexane 4 to 8 times, and then dried in an inert atmosphere (such as nitrogen) at 20 to 30° C. to obtain a hollow fiber membrane.
[0030] In the above technical scheme, the swelling agent used in step (2) is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene, the swelling temperature is 80-120°C, the swelling time is 5-12 hours, and the volume ratio of the swelling agent to the hollow fiber membrane is 2-5.
[0031] In the above technical scheme, the second modifier described in step (2) is a second modifying component (the second modifying component is selected from at least one of 1,3,5-tris[4-(chloromethyl)phenyl]benzene, 1,3,5-trichlorobenzene, and 1,3,5-tris(chloromethyl)benzene), a catalyst and a solvent; the catalyst is selected from one of a Lewis acid or a Lewis base, preferably at least one of anhydrous zinc chloride, anhydrous tin tetrachloride, and anhydrous aluminum chloride; the solvent is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene; in terms of mass fractions, the second modifying component: catalyst: solvent = (5-15): (1-3): (100-200).
[0032] In the above technical solution, the treatment conditions of the treatment with the second modifier in step (2) are as follows: the second modifier flows through the inner cavity of the hollow fiber membrane at a linear velocity of 0.2 m / s to 0.5 m / s, the treatment temperature is 30° C. to 60° C., and the treatment time is 20 to 40 minutes. After the hollow fiber membrane is treated with the second modifier, a modified hollow fiber membrane intermediate is obtained.
[0033] In the above technical scheme, the modified hollow fiber membrane intermediate is subjected to a third modification treatment and a third modification post-treatment to obtain a modified hollow fiber membrane. The third modifier is a third modification component (the third modification component is selected from at least one of N-(carboxymethyl) maleamic acid, 3,4,5-tricarboxylic acid aniline, and 5-(3,5-dicarboxybenzamide)isophthalic acid), sodium hydroxide and a solvent; the solvent is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene; by mass, the third modification component: sodium hydroxide: solvent = (5-15): (1-3): (100-200).
[0034] In the above technical solution, the treatment conditions of the third modifier treatment are as follows: the third modifier passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.2 m / s to 0.5 m / s, the treatment temperature is 40°C to 80°C, and the treatment time is 5 to 15 minutes.
[0035] In the above technical solution, the post-treatment agent used in the third modification post-treatment is a polydimethylsiloxane solution, and the solvent is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene. The mass concentration of the polydimethylsiloxane solution is 2% to 6%. The outer wall of the modified hollow fiber membrane obtained by the third modification post-treatment is coated with polydimethylsiloxane with a thickness of 80 to 160 microns. The third post-modification treatment includes: dip coating the outer wall of the hollow fiber membrane with a polydimethylsiloxane solution with a mass concentration of 2% to 6%, the dip coating time is 2 to 7 seconds, and then drying in a vacuum drying oven at 50°C to 70°C, the pressure (absolute pressure) of the vacuum drying oven is 50 to 80 kPa, and the drying time is 4 to 8 hours; then soaking with a low-carbon alcohol (the low-carbon alcohol is selected from at least one of methanol and ethanol) at a soaking temperature of 40°C to 60°C, 1 to 5 times, and each soaking time is 1 to 3 hours; then soaking with an acid aqueous solution with a mass concentration of 1% to 5% (the acid is selected from at least one of sulfuric acid, hydrochloric acid, and phosphoric acid), the soaking temperature is 40°C to 60°C, the soaking time is 1 to 5 times, and each soaking time is 1 to 3 hours, and the acid aqueous solution is rinsed with desalted water to neutrality after soaking. Wherein, the viscosity of polydimethylsiloxane is 5000 to 10000 centipoise.
[0036] In the above technical solution, the deammoniation washing liquid described in step S2 can be recycled as the washing medium of the washing tower in step S1.
[0037] In the above technical scheme, the ammonia-containing washing liquid obtained in step S1 is pre-treated before step S2, and the pre-treatment is to filter the ammonia-containing washing liquid using a security filter. The security filter is a bag-type and / or folding filter with a filtration accuracy of 3 to 10 microns. The filtration temperature is 10 to 40°C, and the filtration pressure is 0.5 to 1.0 MPaG.
[0038] In the above technical scheme, in step S1, the raw dry gas is derived from catalytic cracking, thermal cracking, delayed coking, and hydrocracking in a refinery. The raw dry gas includes, but is not limited to, ethylene, methane, ethane, propane, propylene, isobutane, n-butane, trans-butene, n-butene, isobutene, cis-butene, oxygen, nitrogen, hydrogen, carbon monoxide, carbon dioxide, acetylene, 1,3-butadiene, alkanes or alkenes with carbon five or more, and also includes ammonia impurities. In the raw dry gas, the volume content of ethylene is 5% to 40%, preferably 10% to 20%. The volume content of ammonia impurities is not less than 100ppm, preferably not less than 600ppm, more preferably not less than 1000ppm, and further, the volume content is not higher than 2000ppm.
[0039] In the above technical solution, in step S1, the water washing tower can be a conventional plate tower or packed tower in the art. The water washing medium and the raw material dry gas are in countercurrent contact in the tower body.
[0040] In the above technical scheme, in step S1, the number of theoretical plates of the water washing tower is 3 to 8, the water washing temperature is 10 to 40°C, and the water washing pressure is 0.5 to 1.0 MPaG. The water washing medium is industrial fresh water, desalted water, or sodium chloride aqueous solution, preferably sodium chloride aqueous solution. The mass concentration of the sodium chloride aqueous solution is 0.1% to 2.0%. The usage ratio of the raw material dry gas to the water washing medium is, by volume, 50 to 80.
[0041] In the above technical scheme, in step S2, the interior of the membrane extraction component is filled with the modified hollow fiber membrane, and the ammonia in the ammonia-containing water washing liquid is permeated and extracted through the modified hollow fiber membrane to reach the outside of the modified hollow fiber membrane, and mass transfer is achieved with the ammonia stripping lean liquid under the promotion of the concentration gradient, and finally the ammonia in the ammonia-containing water washing liquid is transferred to the ammonia stripping lean liquid, so that the ammonia-containing water washing liquid can be continuously deammonified and regenerated.
[0042] In the above technical solution, in step S2, the ammonia stripping lean solution is industrial fresh water, desalted water, or sodium chloride aqueous solution. The mass concentration of the sodium chloride aqueous solution is 100-500 ppm.
[0043] In the above technical solution, in step S1, the feed amount of raw dry gas to the water scrubber is 10000~50000Nm 3 In step S2, the filling amount of the modified hollow fiber membrane regular module is 30-40m 3 The cross-sectional arrangement density of the modified hollow fiber membrane in the modified hollow fiber membrane regular module is 30,000 to 60,000 pieces / m 2 .
[0044] In the above technical solution, in step S2, the temperature at which the ammonia-containing washing liquid contacts the modified hollow fiber membrane is 20-50° C. and the pressure is 0.5-1.0 MPaG.
[0045] In the above technical solution, in step S2, the temperature at which the ammonia stripping lean solution contacts the modified hollow fiber membrane is 20-50° C. and the pressure is 0.5-1.0 MPaG.
[0046] In the above technical solution, in step S2, the ammonia-containing washing liquid and the ammonia stripping lean liquid are in a volume ratio of ammonia-containing washing liquid: ammonia stripping lean liquid = 1: (2 to 6).
[0047] In the above technical solution, in step S3, the ammonia stripping rich solution is degraded by electro-oxidation to obtain a regenerated ammonia stripping lean solution. The mass content of chlorine in the regenerated ammonia stripping lean solution is controlled to be less than 1 ppm (preferably less than 0.5 ppm), and the mass content of ammonia is controlled to be less than 3 ppm. The regenerated ammonia stripping lean solution in step S3 can be recycled as the ammonia stripping lean solution in step S2.
[0048] In the above technical solution, in step S3, the electro-oxidation adopts a titanium-based coating electrode modified with tin, antimony or copper. The preparation method of the titanium-based coating electrode modified with tin, antimony or copper comprises:
[0049] Step I, pretreatment of the titanium plate substrate: polishing the titanium plate substrate with 30-50 mesh white corundum in turn, soaking in a sodium hydroxide aqueous solution with a mass concentration of 30%-40% at 50-80° C. for 1-2 hours, rinsing with desalted water to neutrality, soaking in a sulfuric acid aqueous solution with a mass concentration of 20%-30% at 50-80° C. for 1-2 hours, rinsing with desalted water to neutrality, and storing in a nitrogen atmosphere to obtain a pretreated titanium plate substrate;
[0050] Step II, preparing a coating dipping solution: first, citric acid and ethylene glycol are mixed in a molar ratio of 1:(3-6), and reacted at 60-90° C. for 1-2 hours to obtain a citrate ethylene glycol solution; then, the citrate ethylene glycol solution, tin chloride pentahydrate, antimony trichloride, and copper nitrate trihydrate are mixed in a mass ratio of 1000:(94-98):(2-6):(0.5-2) for 0.5-1.0 hours to obtain a coating dipping solution;
[0051] Step III, scraping 200 to 300 ml per square meter of titanium plate substrate, scraping in an inert atmosphere (such as nitrogen) to obtain a scraping wet plate; drying at 100 to 150 kPaG and 120 to 150° C. for 0.5 to 1.0 hour under an inert atmosphere (such as nitrogen) to obtain a scraping dry substrate;
[0052] Step IV, the above-mentioned scraping dried substrate is roasted in an air roasting furnace at 100-150 kPaG and 500-550° C. for 10-30 minutes to obtain a scraping roasted substrate;
[0053] Step V, repeat steps III and IV 10 to 15 times, and the last calcination conditions are as follows: calcination in an air calcination furnace at 100 to 150 kPaG, 500 to 550°C, for 1 to 2 hours to obtain a titanium-based coating electrode modified with tin, antimony and copper.
[0054] In the above technical solution, in step S3, the electro-oxidation preferably adopts a multi-stage electro-oxidation reactor, further a two-stage to six-stage electro-oxidation reactor, such as a three-stage electro-oxidation reactor, i.e., a first-stage electro-oxidation reactor, a second-stage electro-oxidation reactor, and a third-stage electro-oxidation reactor, and the electrode size in the electro-oxidation reactor is (2-3 meters) × (4-6 meters), and the electrode spacing is 1-3 centimeters. The cathode of the electro-oxidation reactor is a titanium mesh, and the anode is the titanium-based coating electrode modified with tin, antimony, and copper.
[0055] In the above technical solution, in step S3, the electrolyte of the electro-oxidation reactor has a mass concentration of sodium sulfate and sodium chloride of 3% to 6% and 0.1% to 4% respectively, and the rest is desalted water. The linear velocity of the electrolyte on the electrode surface is 0.3 to 0.7 m / s.
[0056] In the above technical solution, in step S3, the electro-oxidation reaction conditions are as follows: voltage is 1.2-1.6 V, current density is 7-50 mA / cm2, operating pressure is 0.5-1.0 MPaG, and operating temperature is 20-40°C.
[0057] In the above technical solution, preferably, when a multi-stage electro-oxidation reactor is used, the current density decreases step by step. Taking a three-stage electro-oxidation reactor as an example, the electro-oxidation reaction conditions are as follows:
[0058] The first-stage electro-oxidation reactor has a voltage of 1.2 to 1.6 volts, a current density of 30 to 50 mA / cm2, an operating pressure of 0.5 to 1.0 MPaG, and an operating temperature of 20 to 40°C;
[0059] The second-stage electro-oxidation reactor has a voltage of 1.2 to 1.6 V, a current density of 15 to 25 mA / cm2, an operating pressure of 0.5 to 1.0 MPaG, and an operating temperature of 20 to 40°C;
[0060] The third-stage electro-oxidation reactor has a voltage of 1.2 to 1.6 V, a current density of 7 to 12 mA / cm2, an operating pressure of 0.5 to 1.0 MPaG, and an operating temperature of 20 to 40°C.
[0061] In the above technical solution, the volume content of ammonia in the deammoniation washing liquid obtained in step S2 is not higher than 10 ppm.
[0062] In the above technical solution, the volume content of ammonia in the deammoniation purified dry gas obtained in step S1 is not higher than 5 ppm, preferably not higher than 3 ppm.
[0063] In the above technical solution, the deammoniation purified dry gas obtained in step S1 can meet the requirements of long-term operation of the ethylbenzene alkylation catalyst.
[0064] A second aspect of the present invention provides a separation system for removing ammonia from dry gas, comprising:
[0065] 1) Water scrubber, used to remove ammonia impurities in the raw dry gas;
[0066] 2) A membrane extraction component, used to extract and remove ammonia impurities from the ammonia-containing washing solution and transfer the mass to the ammonia stripping lean solution;
[0067] 3) Electro-oxidation reactor, used for oxidative removal of ammonia impurities in ammonia stripping rich liquid.
[0068] Compared with the prior art, the present invention has the following advantages:
[0069] 1. The inventors of the present invention have found through research that there are ammonia impurities in the raw dry gas that have a significant impact on the ethylbenzene alkylation catalyst, and the ammonia impurities will be adsorbed on the acid active center, resulting in a decrease in the activity of the ethylbenzene catalyst and a shortened operating cycle. Due to the increase in the specific gravity of low-quality crude oil refining and the volatility of the existing conventional desulfurization and regeneration process, the ammonia impurities in the raw dry gas continue to fluctuate significantly. If only conventional adsorbents (such as ion exchange resins, activated carbon, etc.) are used for fixed bed adsorption, the adsorbent is easily saturated, conventional regeneration operations are frequent, and the amount of wastewater discharged is large. If a water scrubber is directly used to wash water for deammoniation, in order to ensure the deammoniation effect, the consumption of fresh water is extremely large and the cost is high. Furthermore, the degradation rate of ammonia by direct oxidation reaction of hydroxyl radicals is slow. Although ammonia in aqueous solution can be removed by indirect electro-oxidation reaction by adding sodium chloride salt, chlorine gas will be produced due to electrolysis reaction during the indirect electro-oxidation reaction. If chlorine-containing water is used in a water scrubber, the chlorine in the washing water will be decomposed into the raw gas during the washing and ammonia removal process, resulting in "chlorine poisoning" of the catalyst in the subsequent processing technology. In some working conditions, the raw gas contains a certain amount of reducing gas (such as hydrogen). When the strong oxidant produced by the indirect electro-oxidation reaction is in direct contact with the reducing gas, there is a safety hazard. Therefore, the electro-oxidation method cannot be directly used for the regeneration of the washing liquid medium. The inventors have found through further research that the modified hollow fiber membrane of the present invention is used for membrane extraction process through the modified base membrane containing sulfonic acid groups and carboxyl groups, the grafted layer containing carboxyl groups and sulfonic acid groups, and the matching of the hydrophobic dense outer wall with a certain degree of polymerization, which can not only realize the high rate and high selectivity of the membrane to absorb ammonia in the ammonia-containing water washing liquid, but also realize the penetration of the ammonia component into the ammonia stripping lean liquid driven by the concentration difference, while avoiding the contact between the washing medium and the ammonia stripping lean liquid logistics, and the washing medium after deammoniation is returned to the washing tower for recycling, so as to achieve the effect of deammoniation close to fresh water; the ammonia stripping lean liquid logistics isolated from the washing water circulation system can be conveniently processed in depth, and at the same time, it does not cause pollution to the washing water circulation system or raw gas. Preferably, multi-stage electro-oxidation is adopted, and by controlling the operating parameters and sodium chloride concentration of the electro-oxidation reactor, the ammonia in the ammonia stripping rich liquid is effectively removed, the ammonia stripping rich liquid is regenerated, and the residual chlorine in the ammonia stripping lean liquid is reduced, the influence of the residual chlorine on the hollow fiber membrane structure is reduced, and the service life of the hollow fiber membrane is maintained.
[0070] 2. The present invention solves the problems of high ammonia impurity content in the existing raw dry gas that affects the ethylbenzene alkylation catalyst and short operating cycle of the alkylation catalyst, realizes continuous purification and regeneration of wash water and continuous purification and regeneration of stripping solution, greatly improves the operating cycle of the alkylation catalyst and reduces the production cost of ethylbenzene. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 This is a schematic diagram of a separation system for continuously and stably removing ammonia from dry gas according to the present invention;
[0072] The reference numerals are described as follows:
[0073] 101 is a water washing tower, 102 is a security filter, 103 is a membrane extraction component, 104 is an ammonia stripping rich liquid buffer tank, 105 is an electrolyte delivery pump, 106 is a first-stage electro-oxidation reactor, 107 is a second-stage electro-oxidation reactor, 108 is a third-stage electro-oxidation reactor, 109 is an ammonia stripping lean liquid buffer tank, 110 is an ammonia stripping lean liquid delivery pump, 201 is a raw material dry gas inlet, 202 is a deammoniation purified dry gas outlet, 203 is a fresh water washing medium replenishment port, 204 is a fresh electrolyte replenishment port, and 205 is an electrolyte discharge port. DETAILED DESCRIPTION
[0074] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention.
[0075] In the present invention, the analysis of low-carbon hydrocarbon components and ammonia is performed by gas chromatography Agilent 7890A GC (Agilent, USA), equipped with a HP-PLOT Al2O3 KCl (50m×0.53mm×15μm) capillary column, the column temperature is maintained at 100°C for 10 minutes, then increased to 120°C at 30°C per minute, and maintained for 3 minutes. The carrier gas He flow rate is 3mL / min, the injection volume is 0.1mL (quantitative loop), the split ratio is 5:1, the injection port temperature is 250°C, and the detector (FID) temperature is 250°C.
[0076] A separation system for continuously and stably removing ammonia from dry gas according to the present invention (such as Figure 1As shown), it includes: 101 is a water scrubber, 102 is a security filter, 103 is a membrane extraction component, 104 is an ammonia stripping rich liquid buffer tank, 105 is an electrolyte delivery pump, 106 is a first-stage electro-oxidation reactor, 107 is a second-stage electro-oxidation reactor, 108 is a third-stage electro-oxidation reactor, 109 is an ammonia stripping lean liquid buffer tank, and 110 is an ammonia stripping lean liquid delivery pump. The separation process is as follows: the raw dry gas 201 (for example, from catalytic cracking, thermal cracking, delayed coking, and hydrocracking in a refinery) enters the lower part of the water scrubber 101, and contacts with the water scrubbing medium coming from the upper part of the water scrubber 101 in the tower body in countercurrent flow, and ammonia impurities in the raw dry gas are separated and removed. The deammoniation purified dry gas 202 after deammonification enters the subsequent alkylation reaction system to react with benzene to produce ethylbenzene and other components. The ammonia-containing washing liquid in the water washing tower kettle is filtered through the security filter 102 and then enters the membrane extraction component 103 for regeneration. In the membrane extraction component, the ammonia-containing washing liquid passes through the inner cavity of the modified hollow fiber membrane, and the ammonia back-extraction lean liquid passes through the outer wall of the modified hollow fiber membrane. The deammoniation water washing tower washing medium after deammoniation is mixed with part of the fresh water washing medium replenished from the fresh water washing medium replenishing port 203 and then returned to the water washing tower 101 for recycling. The ammonia stripping rich liquid after extracting ammonia from the ammonia-containing washing medium enters the ammonia stripping rich liquid buffer tank 104, and part of the fresh electrolyte replenished from the fresh electrolyte replenishing port 204 is mixed with the ammonia stripping rich liquid, and then transported to the upper or lower part of the first-stage electro-oxidation reactor 106 through the electrolyte delivery pump 105 for primary oxidation, and then flows by gravity to the upper or lower part of the second-stage electro-oxidation reactor 107 for secondary oxidation, and then flows by gravity to the upper or lower part of the third-stage electro-oxidation reactor 108 for tertiary oxidation. The oxidation product of the third-stage electro-oxidation reactor 108 enters the ammonia stripping lean liquid buffer tank 109, and is transported to the electrolyte discharge port 205 through the ammonia stripping lean liquid delivery pump 110 to discharge part of the electrolyte, and then transported to the membrane extraction component 103.
[0077] [Example 1]
[0078] The raw dry gas described in this embodiment is derived from catalytic cracking in a refinery, and the dry gas composition, by volume ratio, includes: 18.7322% methane, 8.5285% ethane, 15.8432% ethylene, 0.1788% propane, 0.8635% propylene, 0.0831% isobutane, 0.0164% normal butane, 0.0070% trans-butene, 0.0195% normal butene, 0.0381% isobutene, 0.0002% cis-butene, 0.1329% oxygen, 13.1458% nitrogen, 28.4233% hydrogen, 1.5636% carbon monoxide, 3.4974% carbon dioxide, 0.0056% acetylene, 0.0001% 1,3-butadiene, 6.6454% hydrogen sulfide, 1.2569% alkanes or alkenes with a carbon content of more than five, 0.0560% ammonia, and 0.9627% other components.
[0079] The separation process of this embodiment is the same as Figure 1 As shown, the method for continuously and stably removing ammonia from dry gas comprises:
[0080] S1) the raw dry gas is passed through a water scrubber to remove ammonia impurities, the top of the tower obtains deammoniation purified dry gas, and the bottom of the tower obtains ammonia-containing water washing liquid;
[0081] S2) the ammonia-containing washing liquid is filtered through a security filter to obtain a pre-treated ammonia-containing washing liquid; the pre-treated ammonia-containing washing liquid is passed through the inner cavity of the modified hollow fiber membrane of the membrane extraction component to obtain a deammoniation washing liquid; the deammoniation washing liquid is continuously used in step S1; the ammonia stripping lean liquid is transferred with the pre-treated ammonia-containing washing liquid through the modified hollow fiber membrane in the shell side of the membrane extraction component to obtain an ammonia stripping rich liquid;
[0082] S3) The ammonia stripping rich liquid is oxidized and degraded step by step in the electro-oxidation reactor to obtain an ammonia stripping lean liquid; the ammonia stripping lean liquid is continuously used in step S2.
[0083] The water washing tower is a plate tower. The water washing medium and the raw material dry gas are in countercurrent contact in the tower body. The theoretical number of plates of the water washing tower is 6, the water washing temperature is 25°C, and the water washing pressure is 0.7MPaG. The water washing medium is a sodium chloride aqueous solution, and the mass concentration of the sodium chloride aqueous solution is 1%. The dosage ratio of the raw material dry gas to the water washing medium is, by volume, 65.
[0084] The security filter is a bag filter with a filtration accuracy of 5 microns. The filtration temperature is 25°C and the filtration pressure is 0.7MPaG.
[0085] The interior of the membrane extraction component is filled with a modified hollow fiber membrane, through which ammonia in the pretreated ammonia-containing water washing liquid is infiltrated and extracted to reach the outside of the modified hollow fiber membrane, and then mass transfer is achieved with the ammonia stripping lean liquid under the promotion of the concentration gradient, and finally ammonia in the pretreated ammonia-containing water washing liquid is transferred to the ammonia stripping lean liquid, so that the pretreated ammonia-containing water washing liquid can be continuously deaminated and regenerated.
[0086] The preparation method of the modified hollow fiber membrane comprises: preparing a casting solution containing a first modifier, a core solution and an outer gel bath, and then forming and drying the hollow fiber membrane by hollow fiber spinning. Then, the hollow fiber membrane is swollen, treated with a second modifier, treated with a third modifier and post-modification treatment to obtain a modified hollow fiber membrane.
[0087] The first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) (molecular weight 5500) and sodium polyanisyl sulfonate (molecular weight 8000), and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is 11:4. The preparation conditions of the hollow fiber membrane are as follows: polypropylene (molecular weight 45000), N-methylpyrrolidone, diethylene glycol, and the first modifier are in a mass ratio of 25:125:4:15, stirred at 100°C for 36 hours, and then allowed to stand for degassing for 7 hours to obtain a casting solution containing the first modifier. The core liquid composition is N-methylpyrrolidone: water = 5:95 in a mass ratio. The outer gel bath composition is desalted water. The inner diameter of the spinneret is 0.6 mm, the outer diameter is 2.4 mm, the temperature of the core liquid and the outer gel bath is 2°C, the air gap height is 3 cm, the collection rate is free fall, the casting liquid flow rate is 8.5 ml / min, the casting liquid pressure in the spinneret is 200 kPa (gauge pressure), the core liquid flow rate is 5 ml / min, the ambient temperature is 25°C, the ambient humidity is 60%, the casting liquid and the core liquid and the outer gel bath undergo solvent exchange and phase separation solidification to form a hollow fiber membrane blank. The hollow fiber blank is washed with desalted water 6 times, methanol 6 times, and n-hexane 6 times, and then dried in a nitrogen atmosphere at 25°C to obtain a hollow fiber membrane.
[0088] The hollow fiber swelling agent was toluene, the swelling temperature was 100° C., the swelling time was 8.5 hours, and the volume ratio of the swelling agent to the hollow fiber membrane was 3.5.
[0089] The second modifier is 1,3,5-trichlorobenzene, anhydrous zinc chloride and toluene, and the mass fraction is 1,3,5-trichlorobenzene: anhydrous zinc chloride: toluene = 10:2:150. The conditions for the second modifier treatment are as follows: the second modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.35 m / s, the treatment temperature is 45°C, and the treatment time is 30 minutes. After the hollow fiber membrane is treated with the second modifier, a modified hollow fiber membrane intermediate is obtained.
[0090] The modified hollow fiber membrane intermediate is subjected to a third modification treatment and a third modification post-treatment to obtain a modified hollow fiber membrane. The third modifier is 3,4,5-tricarboxylic acid aniline, sodium hydroxide and toluene, and the mass fractions are 3,4,5-tricarboxylic acid aniline: sodium hydroxide: toluene = 10:2:150. The conditions for the third modifier treatment are as follows: the third modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.35 m / s, the treatment temperature is 60°C, and the treatment time is 10 minutes.
[0091] The third post-modification treatment includes: using a 4% polydimethylsiloxane (viscosity of 7500 centipoise) toluene solution to dip coat the outer wall of the hollow fiber membrane for 4.5 seconds, followed by drying in a 60°C vacuum drying oven with a pressure (absolute pressure) of 65 kPa for 6 hours; followed by immersion in ethanol at a temperature of 50°C, 3 times, and 1.5 hours each time; followed by immersion in a 3% aqueous sulfuric acid solution at a temperature of 50°C, 3 times, and 1.5 hours each time, and rinsing with desalted water to neutrality after immersion in the aqueous sulfuric acid solution.
[0092] The prepared modified hollow fiber membrane has an inner diameter of 0.6 mm, a base membrane thickness of 0.9 mm, a carboxyl content of 7.5 mmol / g, and a sulfonic acid content of 5.1 mmol / g in the base membrane; the carboxyl content of the grafted layer is 23.3 mmol / g, and the sulfonic acid content is 15.6 mmol / g; and the thickness of the outer wall polydimethylsiloxane is 120 microns.
[0093] In step S1, the feed rate of raw dry gas to the water scrubber is 30000 Nm 3 / hour, the filling capacity of the modified hollow fiber membrane regular module is 35m 3 The cross-sectional arrangement density of the modified hollow fiber membrane in the modified hollow fiber membrane regular module is 45,000 pieces / m 2 . In step S2, the temperature at which the pre-treated ammonia-containing water washing liquid contacts the modified hollow fiber membrane is 35°C and the pressure is 0.7 MPaG. In step S2, the ammonia stripping lean solution is a sodium chloride solution with a mass concentration of 300 ppm. In step S2, the temperature at which the ammonia stripping lean solution contacts the modified hollow fiber membrane is 35°C and the pressure is 0.7 MPaG. In step S2, the ammonia-containing water washing liquid and the ammonia stripping lean solution are in a volume ratio of ammonia-containing water washing liquid: ammonia stripping lean solution = 1:4.
[0094] In step S3, the electro-oxidation reactor is equipped with a titanium-based coating electrode modified by tin, antimony, and copper. The preparation method of the titanium-based coating electrode modified by tin, antimony, and copper includes: step I, pretreatment of the titanium plate substrate, polishing the titanium plate substrate with 40 mesh white corundum in turn, soaking in a sodium hydroxide aqueous solution with a mass concentration of 35% at 65°C for 1.5 hours, rinsing with desalted water to neutrality, soaking in a sulfuric acid aqueous solution with a mass concentration of 25% at 65°C for 1.5 hours, rinsing with desalted water to neutrality, and storing in a nitrogen atmosphere to obtain a pretreated titanium plate substrate. Step II, preparing an immersion solution, first mixing citric acid and ethylene glycol at a molar ratio of 1:4.5, and reacting at 75°C for 1.5 hours to obtain a citrate ethylene glycol solution; then mixing the citrate ethylene glycol solution, tin chloride pentahydrate, antimony trichloride, and copper nitrate trihydrate at a mass ratio of 1000:96:4:1.2 for 0.7 hours to obtain a coating immersion solution. Step III, scrape 250 ml per square meter of titanium plate substrate in a nitrogen atmosphere to obtain a scrape-coated wet plate; the above-mentioned scrape-coated wet plate is dried in a nitrogen drying oven at 125kPaG and 135°C for 0.7 hours to obtain a scrape-coated dry substrate; Step IV, the above-mentioned scrape-coated dry substrate is roasted in an air roasting furnace at 125kPaG and 525°C for 20 minutes, and then naturally cooled to room temperature to obtain a scrape-coated roasted substrate; repeat steps III and IV for 13 times, and the last roasting conditions are as follows: the roasting time is controlled to be 1.5 hours in an air roasting furnace at 125kPaG and 525°C to obtain a titanium-based coating electrode modified with tin, antimony and copper.
[0095] In step S3, the electro-oxidation reactor is composed of a first-stage electro-oxidation reactor, a second-stage electro-oxidation reactor, and a third-stage electro-oxidation reactor. The electrode size in the electro-oxidation reactor is (2.5 meters) × (5 meters), the electrode spacing is 2 centimeters, the cathode is a titanium mesh, and the anode is the above-mentioned titanium-based coating electrode. In step S6, the electrolyte of the electro-oxidation reactor has a mass concentration of sodium sulfate and sodium chloride of 4.5% and 2%, respectively, and the rest is desalted water. The linear velocity of the electrolyte on the electrode surface is 0.5 meters per second. The voltage of the first-stage electro-oxidation reactor is 1.4 volts, the current density is 40 milliamperes per square centimeter, the operating pressure is 0.7 MPaG, and the operating temperature is 30°C. The voltage of the second-stage electro-oxidation reactor is 1.4 volts, the current density is 20 milliamperes per square centimeter, the operating pressure is 0.7 MPaG, and the operating temperature is 30°C. The third-stage electro-oxidation reactor has a voltage of 1.4 V, a current density of 9.5 mA / cm2, an operating pressure of 0.7 MPaG, and an operating temperature of 30° C. The chlorine content in the ammonia stripping lean solution after regeneration reaches 0.5 ppm, and the ammonia content reaches 1.5 ppm.
[0096] The ammonia content in the deammoniation washing liquid obtained in step S2 is 5 ppm. The ammonia content in the deammoniation purified dry gas obtained in step S1 is 3 ppm, which can meet the requirements of long-term operation of the ethylbenzene alkylation catalyst.
[0097] [Example 2]
[0098] The raw dry gas described in this embodiment is the same as that in embodiment 1. The separation process of this embodiment is the same as that in embodiment 1.
[0099] The water washing tower is a plate tower. The water washing medium and the raw material dry gas are in countercurrent contact in the tower body. The theoretical number of plates of the water washing tower is 7, the water washing temperature is 15°C, and the water washing pressure is 0.9MPaG. The water washing medium is a sodium chloride aqueous solution, and the mass concentration of the sodium chloride aqueous solution is 1.8%. The dosage ratio of the raw material dry gas to the water washing medium is, by volume, 55.
[0100] The security filter is a bag filter with a filtration accuracy of 5 microns. The filtration temperature is 15°C and the filtration pressure is 0.9MPaG.
[0101] The interior of the membrane extraction component is filled with a modified hollow fiber membrane, through which ammonia in the pretreated ammonia-containing water washing liquid is infiltrated and extracted to reach the outside of the modified hollow fiber membrane, and then mass transfer is achieved with the ammonia stripping lean liquid under the promotion of the concentration gradient, and finally ammonia in the pretreated ammonia-containing water washing liquid is transferred to the ammonia stripping lean liquid, so that the pretreated ammonia-containing water washing liquid can be continuously deaminated and regenerated.
[0102] The preparation method of the modified hollow fiber membrane comprises: preparing a casting solution containing a first modifier, a core solution and an outer gel bath, and then forming and drying the hollow fiber membrane by hollow fiber spinning. Then, the hollow fiber membrane is swollen, treated with a second modifier, treated with a third modifier and post-modification treatment to obtain a modified hollow fiber membrane.
[0103] The first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) (polymer molecular weight of 5000) and sodium polyanisyl sulfonate (polymer molecular weight of 7000), and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is 14:3. The preparation conditions of the hollow fiber membrane are as follows: polypropylene (molecular weight of 45000), N-methylpyrrolidone, diethylene glycol, and the first modifier are in a mass ratio of 22:145:5:18, stirred at 110°C for 45 hours, and then allowed to stand for degassing for 9 hours to obtain a casting solution containing the first modifier. The core liquid composition is N-methylpyrrolidone: water = 3:97 by mass ratio. The outer gel bath composition is desalted water. The inner diameter of the spinneret is 0.4 mm, the outer diameter is 2.8 mm, the temperature of the core liquid and the outer gel bath is 0.5°C, the air gap height is 3.5 cm, the collection rate is free fall, the casting liquid flow rate is 7.5 ml / min, the casting liquid pressure in the spinneret is 150 kPa (gauge pressure), the core liquid flow rate is 4 ml / min, the ambient temperature is 23°C, the ambient humidity is 65%, the casting liquid and the core liquid, the outer gel bath undergo solvent exchange and phase solidification to form a hollow fiber membrane blank. The hollow fiber embryo was washed with desalted water 7 times, methanol 7 times, and n-hexane 7 times, and then dried in a nitrogen atmosphere at 22°C to obtain a hollow fiber membrane.
[0104] The hollow fiber swelling agent was toluene, the swelling temperature was 110° C., the swelling time was 11 hours, and the volume ratio of the swelling agent to the hollow fiber membrane was 4.
[0105] The second modifier is 1,3,5-trichlorobenzene, anhydrous zinc chloride and toluene, and the mass fraction is 1,3,5-trichlorobenzene: anhydrous zinc chloride: toluene = 14:2.5:120. The conditions for the second modifier treatment are as follows: the second modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.25 m / s, the treatment temperature is 55°C, and the treatment time is 35 minutes. After the hollow fiber membrane is treated with the second modifier, a modified hollow fiber membrane intermediate is obtained.
[0106] The modified hollow fiber membrane intermediate is subjected to a third modification treatment and a third modification post-treatment to obtain a modified hollow fiber membrane. The third modifier is 3,4,5-tricarboxylic acid aniline, sodium hydroxide and toluene, and by weight, 3,4,5-tricarboxylic acid aniline: sodium hydroxide: toluene = 14:2.5:115. The conditions for the third modifier treatment are as follows: the third modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.25 m / s, the treatment temperature is 76°C, and the treatment time is 13 minutes.
[0107] The third post-modification treatment includes: using a 3% polydimethylsiloxane (viscosity of 6000 centipoise) toluene solution to dip coat the outer wall of the hollow fiber membrane for 3 seconds, followed by drying in a 55°C vacuum drying oven with a pressure (absolute pressure) of 75kPa for 7 hours; followed by immersion in ethanol at a temperature of 55°C, 4 immersions, and 2 hours each immersion; followed by immersion in a 4.5% sulfuric acid aqueous solution at a temperature of 55°C, 4 immersions, and 2 hours each immersion, and rinsing with desalted water to neutrality after immersion in the sulfuric acid aqueous solution.
[0108] The prepared modified hollow fiber membrane has an inner diameter of 0.4 mm, a base membrane thickness of 1.2 mm, a carboxyl content of 10.8 mmol / g, and a sulfonic acid content of 7.9 mmol / g in the base membrane; the carboxyl content of the grafted layer is 28.7 mmol / g, and the sulfonic acid content is 22.6 mmol / g; and the thickness of the outer wall polydimethylsiloxane is 90 microns.
[0109] In step S1, the feed rate of raw dry gas to the water scrubber is 30000 Nm 3 / hour, the filling capacity of the modified hollow fiber membrane regular module is 38m 3 The cross-sectional arrangement density of the modified hollow fiber membrane in the modified hollow fiber membrane regular module is 55,000 pieces / m 2 . In step S2, the ammonia stripping lean solution is a sodium chloride solution with a mass concentration of 400ppm. In step S2, the temperature at which the pretreated ammonia-containing water washing solution and the modified hollow fiber membrane are in contact is 45°C and the pressure is 0.9MPaG. In step S2, the temperature at which the ammonia stripping lean solution and the modified hollow fiber membrane are in contact is 45°C and the pressure is 0.9MPaG. In step S2, the ammonia-containing water washing solution and the ammonia stripping lean solution are in a volume ratio of ammonia-containing water washing solution: ammonia stripping lean solution = 1:5.
[0110] In step S3, the electro-oxidation reactor is equipped with a titanium-based coating electrode modified by tin, antimony, and copper. The preparation conditions of the titanium-based coating electrode modified by tin, antimony, and copper are as follows: Step I, pretreatment of the titanium plate substrate, polishing the titanium plate substrate with 35 mesh white corundum in turn, soaking in a sodium hydroxide aqueous solution with a mass concentration of 38% at 75°C for 1.8 hours, rinsing with desalted water to neutrality, soaking in a sulfuric acid aqueous solution with a mass concentration of 27% at 75°C for 1.8 hours, rinsing with desalted water to neutrality, and storing in a nitrogen atmosphere to obtain a pretreated titanium plate substrate. Step II, preparing an immersion solution, first mixing citric acid and ethylene glycol in a molar ratio of 1:4.0, and reacting at 85°C for 1.7 hours to obtain a citrate ethylene glycol solution; then mixing the citrate ethylene glycol solution, tin chloride pentahydrate, antimony trichloride, and copper nitrate trihydrate, by mass, 1000 parts: (97 parts): (5 parts): (1.7 parts) for 0.9 hours to obtain a coating immersion solution. Step III, apply 290 ml of the scraper coating per square meter of the titanium plate substrate in a nitrogen atmosphere to obtain a scraper-coated wet plate; the above-mentioned scraper-coated wet plate is dried in a nitrogen drying oven at 105 kPaG and 125°C for 0.9 hours to obtain a scraper-coated dry substrate; Step IV, the above-mentioned scraper-coated dry substrate is roasted in an air roasting furnace at 105 kPaG and 545°C for 25 minutes, and then naturally cooled to room temperature to obtain a scraper-coated roasted substrate; repeat steps III and IV for 14 times, and for the last roasting, control the roasting time to be 1.8 hours in an air roasting furnace at 105 kPaG and 545°C to obtain a titanium-based coating electrode modified with tin, antimony and copper.
[0111] In step S3, the electro-oxidation reactor is composed of a first-stage electro-oxidation reactor, a second-stage electro-oxidation reactor, and a third-stage electro-oxidation reactor. The electrode size in the electro-oxidation reactor is (2.8 meters) × (5.7 meters), the electrode spacing is 1.5 centimeters, the cathode is a titanium mesh, and the anode is the above-mentioned titanium-based coating electrode modified with tin, antimony, and copper. The electrolyte of the electro-oxidation reactor, in terms of mass concentration, has a mass concentration of 5.5% and 3% of sodium sulfate and sodium chloride, respectively, and the rest is desalted water. The linear velocity of the electrolyte on the electrode surface is 0.4 meters per second. In step S6, the voltage of the first-stage electro-oxidation reactor is 1.5 volts, the current density is 45 milliamperes per square centimeter, the operating pressure is 0.9 MPaG, and the operating temperature is 35°C. In step S3, the voltage of the second-stage electro-oxidation reactor is 1.5 volts, the current density is 23 milliamperes per square centimeter, the operating pressure is 0.9 MPaG, and the operating temperature is 35°C. In step S3, the voltage of the third-stage electro-oxidation reactor is 1.5 V, the current density is 11 mA / cm2, the operating pressure is 0.9 MPaG, and the operating temperature is 35° C. The chlorine content in the ammonia stripping lean solution after regeneration reaches 0.1 ppm, and the ammonia content reaches 0.9 ppm.
[0112] The ammonia content in the deammoniation washing liquid obtained in step S2 is 3 ppm. The ammonia content in the deammoniation purified dry gas obtained in step S1 is 1.2 ppm, which can meet the requirements of long-term operation of ethylbenzene alkylation catalyst.
[0113] [Example 3]
[0114] The raw dry gas described in this embodiment is the same as that in embodiment 1. The separation process of this embodiment is the same as that in embodiment 1.
[0115] The water washing tower is a conventional plate tower in the art. The water washing medium and the raw material dry gas are in countercurrent contact in the tower body. The theoretical number of plates of the water washing tower is 4, the water washing temperature is 35°C, and the water washing pressure is 0.6MPaG. The water washing water is a sodium chloride aqueous solution, and the mass concentration of the sodium chloride aqueous solution is 0.5%. The dosage ratio of the raw material dry gas to the water washing medium is, by volume, 75.
[0116] The security filter is a bag filter with a filtration accuracy of 5 microns. The filtration temperature is 35°C and the filtration pressure is 0.6MPaG.
[0117] The interior of the membrane extraction component is filled with a modified hollow fiber membrane, through which ammonia in the pretreated ammonia-containing water washing liquid is infiltrated and extracted to reach the outside of the modified hollow fiber membrane, and then mass transfer is achieved with the ammonia stripping lean liquid under the promotion of the concentration gradient, and finally ammonia in the pretreated ammonia-containing water washing liquid is transferred to the ammonia stripping lean liquid, so that the pretreated ammonia-containing water washing liquid can be continuously deaminated and regenerated.
[0118] The preparation method of the modified hollow fiber membrane comprises: preparing a casting solution containing a first modifier, a core solution and an outer gel bath, and then performing hollow fiber spinning and drying by a conventional method to obtain a hollow fiber membrane. Then, the hollow fiber membrane is swollen, treated with a second modifier, treated with a third modifier and post-modification treatment to obtain a modified hollow fiber membrane.
[0119] The first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) (molecular weight 6000) and sodium polyanisyl sulfonate (molecular weight 9000), and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is 9:5. The preparation conditions of the hollow fiber membrane are as follows: polypropylene (molecular weight 45000), N-methylpyrrolidone, diethylene glycol, and the first modifier are in a mass ratio of 28:115:3:12, stirred at 90°C for 30 hours, and then allowed to stand for degassing for 6 hours to obtain a casting solution containing the first modifier. The core liquid composition is N-methylpyrrolidone: water = 7:93 by mass ratio. The outer gel bath composition is desalted water. The inner diameter of the spinneret is 0.9 mm, the outer diameter is 2.3 mm, the temperature of the core liquid and the outer gel bath is 2.5°C, the air gap height is 2.5 cm, the collection rate is free fall, the casting liquid flow rate is 9.5 ml / min, the casting liquid pressure in the spinneret is 250 KPa (gauge pressure), the core liquid flow rate is 6 ml / min, the ambient temperature is 28°C, the ambient humidity is 55%, the casting liquid and the core liquid, the outer gel bath undergo solvent exchange and phase solidification to form a hollow fiber membrane blank. The hollow fiber embryo is washed with desalted water 5 times, methanol 5 times, and n-hexane 5 times, and then dried in a nitrogen atmosphere at 27°C to obtain a hollow fiber membrane.
[0120] The hollow fiber swelling agent is toluene, the swelling temperature is 85° C., the swelling time is 6 hours, and the volume ratio of the swelling agent to the hollow fiber membrane is 3.
[0121] The second modifier is 1,3,5-trichlorobenzene, anhydrous zinc chloride and toluene, and the mass fraction is 1,3,5-trichlorobenzene: anhydrous zinc chloride: toluene = 7:1.5:180. The conditions for the second modifier treatment are as follows: the second modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.45 m / s, the treatment temperature is 35°C, and the treatment time is 25 minutes. After the hollow fiber membrane is treated with the second modifier, a modified hollow fiber membrane intermediate is obtained.
[0122] The modified hollow fiber membrane intermediate is subjected to a third modification treatment and a third modification post-treatment to obtain a modified hollow fiber membrane. The third modifier is 3,4,5-tricarboxylic acid aniline, sodium hydroxide and toluene, and the mass fractions are 3,4,5-tricarboxylic acid aniline: sodium hydroxide: toluene = 7:1.5:185. The conditions for the third modifier treatment are as follows: the third modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.45 m / s, the treatment temperature is 45°C, and the treatment time is 6 minutes.
[0123] The third post-modification treatment includes: using a 5% polydimethylsiloxane (viscosity of 9000 centipoise) toluene solution to dip coat the outer wall of the hollow fiber membrane for 6 seconds, followed by drying in a 65°C vacuum drying oven with a pressure (absolute pressure) of 55 kPa for 5 hours; followed by immersion in ethanol at a temperature of 45°C, twice, and each immersion time of 1.2 hours; followed by immersion in a 2% aqueous sulfuric acid solution at a temperature of 45°C, twice, and each immersion time of 1.2 hours, and after immersion in the aqueous sulfuric acid solution, rinse with desalted water until neutral.
[0124] The prepared modified hollow fiber membrane has an inner diameter of 0.9 mm, a base membrane thickness of 0.7 mm, a carboxyl content of 4.3 mmol / g, and a sulfonic acid content of 2.1 mmol / g in the base membrane; the carboxyl content of the grafted layer is 15.4 mmol / g, and the sulfonic acid content is 7.9 mmol / g; and the thickness of the outer wall polydimethylsiloxane is 140 microns.
[0125] In step S1, the feed rate of raw dry gas to the water scrubber is 40000 Nm 3 / hour, the filling capacity of the modified hollow fiber membrane regular module is 32m 3 The cross-sectional arrangement density of the modified hollow fiber membrane in the modified hollow fiber membrane regular module is 40,000 pieces / m 2 . In step S2, the ammonia stripping lean solution is a sodium chloride solution with a mass concentration of 200 ppm. In step S2, the temperature at which the pretreated ammonia-containing water washing solution and the modified hollow fiber membrane are in contact is 25°C and the pressure is 0.6 MPaG. In step S2, the temperature at which the ammonia stripping lean solution and the modified hollow fiber membrane are in contact is 25°C and the pressure is 0.6 MPaG. In step S2, the ammonia-containing water washing solution and the ammonia stripping lean solution are in a volume ratio of ammonia-containing water washing solution: ammonia stripping lean solution = 1:3.
[0126] In step S3, the electro-oxidation reactor is equipped with a titanium-based coating electrode modified by tin, antimony, and copper. The preparation method of the titanium-based coating electrode modified by tin, antimony, and copper comprises: step I, pretreatment of the titanium plate substrate, polishing the titanium plate substrate with 45 mesh white corundum in turn, soaking in a sodium hydroxide aqueous solution with a mass concentration of 32% at 55°C for 1.1 hours, rinsing with desalted water to neutrality, soaking in a sulfuric acid aqueous solution with a mass concentration of 22% at 55°C for 1.2 hours, rinsing with desalted water to neutrality, and storing in a nitrogen atmosphere to obtain the pretreated titanium plate substrate. Step II, preparing the dipping solution, firstly mixing citric acid and ethylene glycol in a molar ratio of 1:5.0, and reacting at 65°C for 1.2 hours to obtain a citrate ethylene glycol solution; then mixing the citrate ethylene glycol solution, tin chloride pentahydrate, antimony trichloride, and copper nitrate trihydrate, by mass, 1000 parts: (95 parts): (3 parts): (0.7 parts) for 0.6 hours to obtain a coating dipping solution. Step III, apply 220 ml of the scraper coating per square meter of the titanium plate substrate in a nitrogen atmosphere to obtain a scraper-coated wet plate; the above-mentioned scraper-coated wet plate is dried in a nitrogen drying oven at 145kPaG and 145°C for 0.6 hours to obtain a scraper-coated dry substrate; Step IV, the above-mentioned scraper-coated dry substrate is roasted in an air roasting furnace at 145kPaG and 515°C for 15 minutes, and then naturally cooled to room temperature to obtain a scraper-coated roasted substrate; repeat steps III and IV for 11 times, and for the last roasting, control the roasting time to be 1.3 hours in an air roasting furnace at 145kPaG and 515°C to obtain a titanium-based coating electrode modified with tin, antimony and copper.
[0127] In step S3, the electro-oxidation reactor is composed of a first-stage electro-oxidation reactor, a second-stage electro-oxidation reactor, and a third-stage electro-oxidation reactor. The electrode size in the electro-oxidation reactor is (2.1 meters) × (4.2 meters), the electrode spacing is 2.5 centimeters, the cathode is a titanium mesh, and the anode is the above-mentioned titanium-based coating electrode modified with tin, antimony, and copper. The electrolyte of the electro-oxidation reactor, in terms of mass concentration, has a mass concentration of sodium sulfate and sodium chloride of 3.5% and 1%, respectively, and the rest is desalted water. The linear velocity of the electrolyte on the electrode surface is 0.6 meters per second. The voltage of the first-stage electro-oxidation reactor is 1.3 volts, the current density is 35 milliamperes per square centimeter, the operating pressure is 0.6 MPaG, and the operating temperature is 21°C. The voltage of the second-stage electro-oxidation reactor is 1.3 volts, the current density is 16 milliamperes per square centimeter, the operating pressure is 0.6 MPaG, and the operating temperature is 21°C. The third-stage electro-oxidation reactor has a voltage of 1.3 V, a current density of 8 mA / cm2, an operating pressure of 0.6 MPaG, and an operating temperature of 21° C. The chlorine content in the ammonia stripping lean solution after regeneration reaches 0.7 ppm, and the ammonia content reaches 2.2 ppm.
[0128] The ammonia content in the deammoniation washing liquid obtained in step S2 is 8 ppm. The ammonia content in the deammoniation purified dry gas obtained in step S1 is 4.7 ppm, which can meet the requirements of long-term operation of ethylbenzene alkylation catalyst.
[0129] [Example 4]
[0130] The separation process for the raw dry gas in this embodiment is the same as that in Embodiment 2. The only difference between this embodiment and Embodiment 2 is the raw dry gas used. The dry gas composition, by volume, includes: methane 18.4280%, ethane 7.6138%, ethylene 16.0519%, propane 0.1725%, propylene 0.8638%, isobutane 0.0810%, n-butane 0.0163%, trans-butene 0.0069%, n-butene 0.0192%, isobutene 0.0377%, cis-butene 0.0002%, oxygen 0.1334%, nitrogen 13.2409%, hydrogen 29.9967%, carbon monoxide 1.5357%, carbon dioxide 3.2119%, acetylene 0.0055%, 1,3-butadiene 0.0001%, hydrogen sulfide 6.5248%, alkanes or alkenes with a carbon content of more than five carbon atoms 1.1821%, ammonia 0.0113%, and other components 0.8664%.
[0131] The ammonia content in the deammoniation aqueous solution obtained in step S2 is 1 ppm. The ammonia content in the deammoniation purified dry gas obtained in step S1 is 0.1 ppm, which can meet the requirements of long-term operation of ethylbenzene alkylation catalyst.
[0132] [Example 5]
[0133] The separation process for the raw dry gas in this embodiment is the same as that in Embodiment 2. The only difference between this embodiment and Embodiment 2 is the raw dry gas used. The dry gas composition, by volume, includes: methane 16.8604%, ethane 8.3524%, ethylene 17.3045%, propane 0.1764%, propylene 0.8117%, isobutane 0.0763%, n-butane 0.0165%, trans-butene 0.0071%, n-butene 0.0179%, isobutene 0.0361%, cis-butene 0.0002%, oxygen 0.1372%, nitrogen 13.6905%, hydrogen 27.9388%, carbon monoxide 1.5623%, carbon dioxide 3.4286%, acetylene 0.0053%, 1,3-butadiene 0.0001%, hydrogen sulfide 7.1986%, alkanes or alkenes with a carbon content of more than five carbon atoms 1.2924%, ammonia 0.1087%, and other components 0.9780%.
[0134] The ammonia content in the deammoniation aqueous solution obtained in step S2 is 9 ppm. The ammonia content in the deammoniation purified dry gas obtained in step S1 is 4.8 ppm, which can meet the requirements of long-term operation of ethylbenzene alkylation catalyst.
[0135] [Comparative Example 1]
[0136] The dry gas raw material used in this comparative example is the same as that in Example 3, and the alkaline impurities are removed by water washing in a packed tower. The equipment and process operating conditions of the water washing tower are as follows: the temperature is 35°C, the pressure (gauge pressure) is 1000 kPa, the number of theoretical plates is 18, a dilute phosphoric acid aqueous solution with a pH of 3 is used, and the gas-liquid volume ratio is 40.
[0137] The volume content of ammonia in the obtained ammonia-purified dry gas was 82 ppm.
[0138] [Comparative Example 2]
[0139] This comparative example uses commercial SQD-67 resin (H type) (Suqing Resin Company) as the adsorbent and adopts a conventional fixed bed adsorption process. The adsorption conditions are as follows: the resin filling volume is 500 cubic meters, the adsorption temperature is 30°C, and the volume space velocity is 50h -1 .
[0140] The dry gas raw material is the same as that in Example 3. In the initial stage of operation, the volume content of ammonia in the obtained propylene-removed purified dry gas is 4 ppm, and the adsorbent breaks through after about 9 days, and regeneration requires 4% to 6% sulfuric acid regeneration, and the volume consumption of regeneration liquid per unit volume of adsorbent is 4 to 5 times.
[0141] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for continuously removing trace ammonia from dry gas, comprising: S1, the raw dry gas is washed with water to remove ammonia impurities through a water washing tower, the deammoniation purified dry gas is obtained at the top of the tower, and the ammonia-containing washing liquid is obtained at the bottom of the tower; S2, stripping the ammonia-containing water washing liquid using a membrane extraction assembly equipped with a modified hollow fiber membrane, wherein the ammonia-containing water washing liquid and the ammonia stripping lean solution flow through the inner cavity and outer wall of the modified hollow fiber membrane respectively to obtain a deammoniation water washing liquid and an ammonia stripping rich solution; S3, the ammonia stripping rich solution is degraded by electro-oxidation to obtain a regenerated ammonia stripping lean solution; The modified hollow fiber membrane described in step S2 includes a base membrane, a grafted layer and an outer wall, wherein the base membrane has a carboxyl content of 3.8 to 11.2 mmol / g and a sulfonic acid content of 1.9 to 8.4 mmol / g; the grafted layer has a carboxyl content of 14.4 to 32.4 mmol / g and a sulfonic acid content of 7.2 to 24.3 mmol / g; and the outer wall is a polydimethylsiloxane layer with a thickness of 80 to 160 microns.
2. The method according to claim 1, characterized in that The viscosity of the polydimethylsiloxane is 5000 to 10000 centipoise.
3. The method according to claim 1, characterized in that The inner diameter of the modified hollow fiber is 0.3-1.0 mm, and / or the thickness of the base membrane is 0.4-1.5 mm.
4. The method according to claim 3, characterized in that The base film is a polypropylene film modified by a first modifier; the first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) and sodium polyanisenesulfonate, and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisenesulfonate is (8-15):(2-6).
5. The method according to claim 3, characterized in that The molecular weight of the sodium poly(4-styrenesulfonic acid-co-maleic acid) is 4000-7000, and the molecular weight of the sodium polyanisyl sulfonate is 6000-10000.
6. The method according to claim 3, characterized in that The molecular weight of the polypropylene is 40,000-50,000.
7. The method according to any one of claims 1 to 6, characterized in that: The method for preparing the modified hollow fiber membrane comprises: (1) preparing a casting solution containing a first modifier, a core solution and an outer gel bath, and then forming the hollow fiber membrane by hollow fiber spinning and drying, thereby obtaining a hollow fiber membrane, i.e., a base membrane; (2) Swelling the hollow fiber membrane, treating it with a second modifier, and treating it with a third modifier to form a graft layer; (3) The hollow fiber membrane covered with the grafted layer obtained in step (2) is subjected to a third post-modification treatment to cover the hollow fiber membrane with a polydimethylsiloxane layer to obtain a modified hollow fiber membrane.
8. The method according to claim 7, characterized in that The first modifier described in step (1) is sodium poly(4-styrenesulfonic acid-co-maleic acid) and sodium polyanisyl sulfonate, and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is (8-15):(2-6).
9. The method according to claim 8, characterized in that In the first modifier described in step (1), the molecular weight of sodium poly(4-styrenesulfonic acid-co-maleic acid) is 4000-7000, and the molecular weight of sodium polyanisyl sulfonate is 6000-10000.
10. The method according to claim 7, characterized in that The casting liquid containing the first modifier in step (1) comprises: polypropylene, N-methylpyrrolidone, diethylene glycol, and the first modifier, wherein the mass ratio of polypropylene, N-methylpyrrolidone, diethylene glycol, and the first modifier is (20-30): (100-150): (2-6): (10-20); the core liquid is an N-methylpyrrolidone solution, wherein the mass concentration of the N-methylpyrrolidone solution is 2% to 8%.
11. The method according to claim 10, characterized in that In the casting solution containing the first modifier in step (1), the molecular weight of polypropylene is 40,000 to 50,000.
12. The method according to claim 7, characterized in that The swelling agent used in step (2) is selected from at least one of toluene, p-xylene, m-xylene and o-xylene, the swelling temperature is 80-120° C., the swelling time is 5-12 hours, and the volume ratio of the swelling agent to the hollow fiber membrane is 2-5; And / or, the second modifier in step (2) is a second modifying component, a catalyst and a solvent; the second modifying component is selected from at least one of 1,3,5-tris[4-(chloromethyl)phenyl]benzene, 1,3,5-trichlorobenzene and 1,3,5-tris(chloromethyl)benzene; the catalyst is selected from one of Lewis acids or Lewis bases; the solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene; And / or, the treatment conditions of the treatment with the second modifier are as follows: the second modifier passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.2 m / s to 0.5 m / s, the treatment temperature is 30°C to 60°C, and the treatment time is 20 to 40 minutes.
13. The method according to claim 12, characterized in that In the second modifier described in step (2), the catalyst is at least one of anhydrous zinc chloride, anhydrous tin tetrachloride, and anhydrous aluminum chloride.
14. The method according to claim 12, characterized in that In the second modifier, the second modification component: catalyst: solvent = (5-15): (1-3): (100-200) by weight.
15. The method according to claim 7, characterized in that The third modifier is a third modifying component, sodium hydroxide and a solvent; the third modifying component is selected from at least one of N-(carboxymethyl)maleamic acid, 3,4,5-tricarboxylic acid aniline and 5-(3,5-dicarboxybenzamide)isophthalic acid; the solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene; And / or, the treatment conditions of the third modifier treatment are as follows: the third modifier passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.2 m / s to 0.5 m / s, the treatment temperature is 40°C to 80°C, and the treatment time is 5 to 15 minutes.
16. The method according to claim 15, characterized in that In the third modifier, the third modifying component is sodium hydroxide: solvent = (5-15): (1-3): (100-200) by weight.
17. The method according to claim 7, characterized in that The post-treatment agent used in the third modification post-treatment is a polydimethylsiloxane solution with a mass concentration of 2% to 6%, and the solvent is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene; the outer wall of the modified hollow fiber membrane obtained by the third modification post-treatment is polydimethylsiloxane with a thickness of 80 to 160 microns; the viscosity of the polydimethylsiloxane is 5000 to 10000 centipoise.
18. The method according to claim 1, characterized in that The deammoniation washing liquid described in step S2 is circulated and used as the washing medium of the washing tower in step S1.
19. The method according to claim 18, characterized in that The ammonia-containing washing liquid obtained in step S1 is pretreated before step S2, wherein the pretreatment is to filter the ammonia-containing washing liquid using a security filter; the security filter is a bag-type and / or folding filter with a filtration accuracy of 3 to 10 microns; the filtration temperature is 10 to 40°C, and the filtration pressure is 0.5 to 1.0 MPaG.
20. The method according to claim 1, characterized in that In step S1, the volume content of ammonia impurities in the raw dry gas is not less than 100 ppm.
21. The method according to claim 20, characterized in that In step S1, the volume content of ammonia impurities in the raw dry gas is not less than 600 ppm.
22. The method according to claim 20, characterized in that In step S1, the volume content of ammonia impurities in the raw dry gas is not less than 1000 ppm.
23. The method according to claim 20, characterized in that In step S1, the volume content of ammonia impurities in the raw dry gas is not higher than 2000 ppm.
24. The method according to claim 1, characterized in that In step S1, the water washing tower is a plate tower or a packed tower, and the water washing medium and the raw material dry gas are in countercurrent contact in the tower body.
25. The method according to claim 24, characterized in that In step S1, the theoretical number of plates of the water washing tower is 3 to 8, the water washing temperature is 10 to 40° C., and the water washing pressure is 0.5 to 1.0 MPaG; the water washing medium is industrial fresh water, desalted water or sodium chloride aqueous solution; and the usage ratio of the raw material dry gas to the water washing medium is 50 to 80 by volume.
26. The method according to claim 25, characterized in that In step S1, the mass concentration of the sodium chloride aqueous solution is 0.1% to 2.0%.
27. The method according to claim 1, characterized in that In step S2, the ammonia stripping lean solution is industrial fresh water, desalted water or sodium chloride aqueous solution; the mass concentration of the sodium chloride aqueous solution is 100-500 ppm.
28. The method according to claim 1, characterized in that In step S2, the temperature at which the ammonia-containing washing liquid contacts the modified hollow fiber membrane is 20-50°C, and the pressure is 0.5-1.0 MPaG; the temperature at which the ammonia stripping lean liquid contacts the modified hollow fiber membrane is 20-50°C, and the pressure is 0.5-1.0 MPaG; the volume ratio of the ammonia-containing washing liquid to the ammonia stripping lean liquid is ammonia-containing washing liquid: ammonia stripping lean liquid = 1: (2-6).
29. The method according to claim 1, characterized in that In step S3, the electro-oxidation uses a titanium-based coating electrode modified with tin, antimony, or copper; And / or, in step S3, the electro-oxidation reaction conditions are as follows: voltage of 1.2 to 1.6 V, current density of 7 to 50 mA / cm2, operating pressure of 0.5 to 1.0 MPaG, and operating temperature of 20 to 40°C.
30. The method according to claim 29, characterized in that The electro-oxidation adopts a multi-stage electro-oxidation reactor, wherein the current density decreases step by step.
31. The method according to claim 30, characterized in that When a three-stage electro-oxidation reactor is used, the current density of the first electro-oxidation reactor is 30 to 50 mA / cm2, the current density of the second electro-oxidation reactor is 15 to 25 mA / cm2, and the current density of the third electro-oxidation reactor is 7 to 12 mA / cm2.
32. The method according to claim 1 or 29, characterized in that The regenerated ammonia stripping lean liquid in step S3 is recycled as ammonia stripping lean liquid in step S2; and / or, the volume content of ammonia in the deammoniation washing liquid obtained in step S2 is not higher than 10 ppm; And / or, the volume content of ammonia in the deammoniation purified dry gas obtained in step S1 is not higher than 5 ppm.
33. The method according to claim 32, characterized in that The volume content of ammonia in the deammoniation purified dry gas obtained in step S1 is not higher than 3 ppm.
34. A separation system for removing ammonia from dry gas, comprising: 1) Water scrubber, used to remove ammonia impurities in raw dry gas; 2) A membrane extraction component, used for extracting and removing ammonia impurities in the ammonia-containing washing liquid, and transferring mass to the ammonia stripping lean liquid; wherein the membrane extraction component is a membrane extraction component of the modified hollow fiber membrane in any one of claims 1 to 17; 3) Electro-oxidation reactor, used to oxidatively remove ammonia impurities from the ammonia stripping rich liquid.
Citation Information
Patent Citations
System and method for preparing ethylbenzene from refinery dry gas
CN109574780A
Improved preparation method of polypropylene hollow fiber separation membrane
CN103007784A
Method for converting topped-oil type light hydrocarbons
CN106867563A